Solar elastosis and cutaneous melanoma: A site‐specific analysis. Issue 12 (26th November 2014) - Kvaskoff, Marina; Pandeya, Nirmala; Green, Adèle C.; Perry, Susan; Baxter, Catherine; Davis, Marcia B.; Mortimore, Rohan; Westacott, Lorraine; Wood, Dominic; Triscott, Joe; Williamson, Richard; Whiteman, David C.
<x xml:space="preserve">Abstract</x> Cutaneous melanomas are postulated to arise through at least two causal pathways, namely the "chronic sun exposure" and "nevus" pathways. While chronic sun exposure probably causes many head/neck melanomas, its role at other sites is unclear. In a population‐based, case‐case comparison study conducted in Brisbane, Australia, we determined the prevalence and epidemiologic correlates of chronic solar damage in skin adjacent to invasive, incident melanomas on the trunk (n = 418) or head/neck (n = 92) among patients aged 18–79 in 2007–2010. Participants self‐reported information about environmental and phenotypic factors, and a dermatologist counted nevi and actinic keratoses. Dermatopathologists assessed solar elastosis adjacent to each melanoma using a four‐point scale (nil, mild, moderate, marked), and noted the presence or absence of adjacent neval remnants. We measured associations between various factors and solar elastosis using polytomous logistic regression. Marked or moderate solar elastosis was observed in 10% and 27%, respectively, of trunk melanomas, and 60% and 17%, respectively, of head/neck melanomas. At both sites, marked elastosis was positively associated with age (ptrend < 0.0001) and inversely associated with neval remnants (ptrend < 0.001). For trunk melanomas, marked elastosis was associated with highest quartiles of total sun exposure [odds‐ratio (OR) = 5.47, 95% confidence interval (CI) = 1.08–27.60] and facial freckling (OR = 2.98, 95% CI = 1.17–7.56), and inversely associated with deeply tanning skin (OR = 0.29, 95% CI = 0.08–1.11) and high nevus counts (OR = 0.08, 95% CI = 0.01–0.66). Mostly similar associations were observed with moderate solar elastosis. About one in three trunk melanomas in Queensland have evidence of moderate‐to‐marked sun damage, and they differ in risk associations from those without.